THE RELATIONSHIP BETWEEN HUMAN SPIRITUALITY AND THE FUNCTIONAL STATE OF THE CARDIO-RESPIRATORY SYSTEM - Savchenko, V. M.; Kharchenko, H. D.; Tymchyk, O. V. (Rehabilitation and Recreation, 2024)
Aim is to determine the level of spirituality of a person in terms of personal maturity and to investigate its connection with the functional state of the cardio-respiratory system. Material and methods. A total of 560 research participants were examined, 301 (53.75%) of whom were men, and 259 (46.25%) of whom were women. The average age of the examined people was (M±S) 35.00±17.75 (95% confidence interval is 33.52 to 36.47 years of age). There were 337 (60.18%) of patients who were treated in the rehabilitation departments of medical institutions, and 223 (39.82%) of healthy persons (students of the Humanities University). Spirituality was assessed by determining the level of maturity of consciousness and self-awareness of the individual according to Jose Stevens (1994, 2019). The following levels of spirituality were applied in terms of personal maturity: undifferentiated, low (“infant” + “toddler”), medium-low (“child”), medium-high (“adolescent /young man”), high (“adult”) and various combined levels. Anthropometric measurements included body mass and height. The function of the circulatory and respiratory organs of the research participants was assessed according to the following parameters: resting heart rate (RHR), resting respiratory rate, systolic and diastolic blood pressure (BP), forced vital capacity (FVC). Results. The following patterns were established between a person’s spirituality and the functional state of the cardio-respiratory system: research participants with the highest heart rate have the most cases of a low level of spirituality, and research participants with the lowest heart rate (at the limit of statistical significance) have the least cases of this level of spirituality; research participants with high systolic blood pressure have the most cases of undifferentiated and low levels of spirituality, and research participants with low systolic blood pressure have the most cases of medium-high level of spirituality; research participants with high diastolic blood pressure have the most cases of low level of spirituality, and research participants with low blood pressure have the most cases of medium-high level of spirituality; research participants with the lowest FVC have the most cases of a low level of spirituality; research participants with the shortest length of inspiratory breath-holding time have the most cases of undifferentiated and low levels of spirituality. Conclusions. The functional capabilities of the cardio-respiratory system are significantly related to the level of a person’s spirituality: persons with a good/normal functional state have mostly high levels of spirituality, and persons with a poor functional state have low and undifferentiated levels of spirituality; sick people, compared to healthy people, are mostly characterized by low levels of spirituality.